Writing from the Self: Reflecting on the Role of Creative Writing in the Academic Writing Classroom (2020)
As academic writing teachers, we are often faced with the challenge of teaching writing as a system or emancipating from its structures. In this reflective paper, we begin by examining our own experiences with writing for academic and creative purposes using co/autoethnography as a method of self-reflection. In addition, we invited three modern language students at a public university in Tunja, Colombia to share their reflections about their writing processes and the role creative writing could play in the academic writing classroom. Our reflections were a first step in rethinking our classroom from a critical sociocultural model, which revealed that students’ individual writing processes, motivation, feedback, and creative writing could help boost students’ self-confidence when writing for academic purposes.